Guidance and Counseling Model Based on Religious Education to Address Psychosocial Issues in Schools - Rahmatullah, Aulia (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2024)
This article explores the development of a guidance and counseling model based on religious education to address psychosocial issues in schools. The study employs a qualitative approach using literature review and library research methodologies to identify the potential intersection between religious teachings and counseling practices in fostering students' emotional and psychological well-being. By examining existing theories and practices in both religious education and counseling, the study demonstrates how religious values, such as compassion, empathy, and moral responsibility, can be integrated into counseling strategies to address common psychosocial challenges faced by students, including stress, bullying, and identity crises. The findings suggest that a counseling model informed by religious education can provide students with both spiritual and psychological support, promoting resilience, ethical decision-making, and personal growth. Additionally, the integration of religious principles in counseling offers a more holistic approach, catering to the spiritual and emotional needs of students. This research highlights the importance of incorporating religious education in the counseling process to better equip students with the necessary tools for managing their psychosocial issues and navigating the complexities of modern school environments. The article contributes to the field by proposing a framework for school counselors that combines both educational and religious perspectives in addressing the psychological needs of students.